Super Light Water Reactors and Super Fast Reactors Supercritical-Pressure Light Water Cooled Reactors - Oka, Yoshiaki; Koshizuka, Seiichi; Ishiwatari, Yuki.; Yamaji, Akifumi; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
Super Light Water Reactors and Super Fast Reactors provides an overview of the design and analysis of nuclear power reactors. Readers will gain an understanding of the conceptual design elements and specific analysis methods for supercritical-pressure light water cooled reactors. Nuclear fuel, reactor core, plant control, plant stand-up and stability are among the topics discussed, in addition to safety system and safety analysis parameters. Providing the fundamentals of reactor design criteria and analysis, this volume is a useful reference for engineers, industry professionals, and graduate students involved with nuclear engineering and energy technology.
and Overview -- Core Design -- Plant System Design -- Plant Dynamics and Control -- Plant Startup and Stability -- Safety -- Fast Reactor Design -- Research and Development.
Keywords: Engineering; Nuclear chemistry; Nuclear physics; Electric engineering; Nuclear engineering; Engineering; Nuclear Engineering; Nuclear Chemistry; Nuclear Physics, Heavy Ions, Hadrons; Energy Technology; Nuclear Energy